Electrical characterisation of Ruthenium Schottky contacts on n- Ge (1 0 0) - Chawanda, Albert; Nyamhere, Cloud; Nel, Jacqueline M; Francois D, Auret; Mtangi, Wilbert; Mmatsae, Diale (Elservier, 2014)
Abstract in the article